Quality Control of Chinese Medicine Based on Technology Innovation - Wan, PhD, Jianbo; Li, PhD, Shaoping; Wang, PhD, Yitao; Liu, MD, PhD, Jing; Kang, MD, PhD, Jing X. (North American Journal of Medicine and Science, 2009)
With the aim to promote the establishment of international standardization of Chinese medicine (CM), the key scientific techniques, including the selection of the markers, preparation of reference chemical compounds, and the optimization of evaluation methods for standardization of quality control of CM, were discussed and explored in the present paper. A systematic strategy was used to develop the quality control of several CMs attributed to “Huo xue hua yu” and “Fu zheng gu ben”. The key techniques and approaches being used included computational clustering analysis of chromatographic data, biochromatographic technique for identification of biological active compound, the combination of different separation techniques for preparation of reference compound, the application of Pressurized Liquid Extraction (PLE) technique for raw herbal sample preparation, and the optimization of quality control analytical techniques. The results showed that the strategy is feasible for the quality control of CM.